Pengaruh kegiatan literasi kampus mengajar terhadap hasil belajar - Aliyah, Siti Nur; Alwahid, Muhamad Azhar; Gunawan, Asep (Program Studi Magister Pendidikan Agama Islam, 2025)
Literacy is an important foundation in education. However, there are still many students who do not have good literacy skills. This can be caused by various factors, such as lack of interest in reading which has an impact on learning outcomes. The Campus Teaching Program is a strategic effort to improve the quality of education in improving literacy. The objectives of this study were (1) to determine the literacy activities of students in the campus teaching program (2) to determine the learning outcomes of class VIII students of Al-Azhar Plus Bogor Middle School (3) to determine the effect of literacy activities in the campus teaching program on the learning outcomes of class VIII students of Al-Azhar Plus Bogor Middle School. Quantitative research with an associative approach using questionnaires and documentation. In this study, literacy activities had a significant effect on learning outcomes (regression coefficient 0.315; sig. 0.039 <0.05), although its contribution was only 1.1%. Campus Teaching Literacy is effective in improving learning outcomes, but it needs to be supported by other factors such as motivation and learning methods. Abstrak Literasi merupakan fondasi penting dalam pendidikan. Namun, masih banyak siswa yang belum memiliki kemampuan literasi yang baik. Hal ini dapat disebabkan oleh berbagai faktor, seperti kurangnya minat baca yang berdampak pada hasil belajar. Program Kampus Mengajar merupakan upaya strategis untuk meningkatkan kualitas pendidikan dalam meningkatkan literasi. Tujuan penelitian ini adalah (1) mengetahui kegiatan literasi siswa/i program kampus mengajar (2) mengetahui hasil belajar siswa/i kelas VIII SMP Al-Azhar Plus Bogor (3) mengetahui pengaruh kegiatan literasi program kampus mengajar terhadap hasil belajar siswa/i kelas VIII SMP Al-Azhar Plus Bogor. Penelitian kuantitatif dengan pendekatan asosiatif menggunakan angket dan dokumentasi. Dalam penelitian ini kegiatan literasi berpengaruh signifikan terhadap hasil belajar (koefisien regresi 0,315; sig. 0,039 < 0,05), meskipun kontribusinya hanya 1,1%. Literasi Kampus Mengajar efektif meningkatkan hasil belajar, namun perlu didukung faktor lain seperti motivasi dan metode pembelajaran.